Vliyanie biopreparata "Polien" na vnytrieritrotsitarnii metabolism u sportsmenov pri vozdeistvii intenzivnyck fizicheskikh nagruzok - Popichev, M. I.; Konoshenko, S. V.; Tolkacheva, N. V.; Zhurba, V. A.; Petruhin, V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the peculiarities of the intraerythrocyte metabolism in athletes taking the biological compound "Poliyen", when intensive physical loads' influencing. Basing on the results of the research it is concluded that some new compensatory - adaptative reactions perform in an athlete's organism under the influence of the increased expediture of energy. It leads to changes in the intraerythrocytes metabolism in the direction to ensure the erythrocytory membrane's optimal functioning and the effective supply of the organism's tissues by oxygen.